Illustrations for Encyclopedia Erupting Mountain Theme - Purmaningrum Maeni (Universitas Pasundan, 2021)
Indonesia is a country that has a great potential for natural disasters, because of the location of geographic and others. Indonesia's geographical location in the growth zone of three plates namely Eurasia, Indo-Australia and Pacifica or commonly known as ring of fire, causes Indonesia to have many active volcanoes. This makes Indonesia vulnerable to natural disasters earthquakes, erupting mountains, tsunamis and others. To collect detailed actual information that describes the symptoms of nature as well as the situation of social symptom conditions then this research is carried out with descriptive qualitative and quantitative research methods. Illustration design is conveyed through drawings, illustrations, or photos about disaster situations and conditions that are equipped with narratives though effective language. It is expected that by the illustrations through visual images and combined with the narrative the interest of students, especially children can be more aroused so that the information presented can be more quickly captured and understood. The design of an encyclopedic book illustration that is useful as a support for Social Science lessons themed on natural disasters, especially erupting mountains. With the availability of the book Encyclopedia of Mount Erupting for elementary school students, it is expected that knowledge about the erupting mountain can be conveyed interestingly so that children can have better understanding of the causes and how to deal with the disaster of erupting mountains.